Analysis of Tensile Strength on ST.37 Material with SMAW Welding Variations of SAE 10 Oil and Water Cooling - Efrata Tarigan; Alexander Sebayang; Liwat Tarigan; Benar Surbakti (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
In welding work must pay attention to the suitability of the welding construction in order to achieve optimal results. For this reason, welding needs to pay attention to several important things including welding efficiency, energy savings, and of course low costs. The purpose of this study was to determine how the tensile strength of the ST 37 material welded by SMAW welding which was cooled with a variety of cooling media, oil and pure water. The research method used in this research is to use real experimental research methods (True Experimental Research). From the results of the study, it can be concluded that the highest Ultimate Stress (Tu) tensile strength value is when the material is cooled with oil media, where the highest value is 365.15 N/mm2, followed by water cooling media oil, where the highest value is of 347.75 N/mm2, and the lowest is without cooling media where the highest value is 343.35 N/mm2. This is due to the thermal cycle that affects the microstructure of the material, this is what causes the tensile strength of the material to increase when a cooling medium is applied to the ST 37 welding material.